IMPLEMENTASI PERATURAN DAERAH KABUPATEN ROKAN HILIR NOMOR 3 TAHUN 2014 TENTANG KETERTIBAN UMUM TERHADAP RUMAH DI BANTARAN SUNGAI DESA TELUK NILAP KECAMATAN KUBU BABUSSALAM - Hafis Hafis; Emilda Firdaus; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
One of the Regional Regulations which is a public policy related to controlling house buildings on the banks of the river is the Rokan Hilir Regency Regional Regulation Number 3 of 2014 concerning Public Order. The conditions seen in the field are that the implementation needs to be carried out firmly by the Regional Government. The establishment of the Rokan Hilir Regency Regional Regulation Number 3 of 2014 concerning Public Order departs from the problems that occur in Rokan Hilir Regency, namely that there are still many residents who build houses on the banks of the river, which is actually contrary to the Regional Regulation. Therefore, the purpose of this study is, firstly, to determine the implementation of the Rokan Hilir District Regulation Number 3 of 2014, secondly to determine the inhibiting factors, and thirdly to determine the efforts to overcome houses on the riverbanks of TelukNilap Village, Kubu Babussalam District.  This research uses sociological juridical research. The research location is in Teluk Nilap Village, Kubu Babussalam District, namely the Regional House of Representatives of Rokan Hilir Regency, the Civil Service Police Unit of Rokan Hilir Regency and the Teluk Nilap Village Office, while the population and sample are all parties related to the problem being studied. This study used data sources in the form of primary data and secondary data, and data collection techniques were carried out by interviews, observations, and questionnaires. From this research, there are three main points that can be concluded. First, the implementation of the Rokan Hilir District Regulation Number 3 of 2014 concerning public order, especially Article 18paragraph 1, has not been carried out properly. This is because the Regional Regulation of Rokan HilirRegency No. 3 of 2014 concerning public order has not been socialized to the people who live on the riverbanks of Teluk Nilap Village. Second, the inhibiting actor in the implementation of the Rokan Hilir District Regulation Number 3 of 2014 concerning Public Order in Teluk Nilap Village is due to legal factors, law enforcement, legal culture, budget, legal socialization, lack of human resources (HR) in the district Satpol PP work environment. Downstream. Third, future efforts that can be made towards the implementation of Regional Regulation Number 3 of 2014 concerning Public Order are by controlling houses on the riverbanks of Teluk Nilap Village, providing socialization, and improving facilities andinfrastructure in an effort to implement Regional Regulation Number 3 of 2014 about public order. Keywords: Implementation - Public Order - Riverbanks